Can AI Predict Drug Response Based on Genetic Profiles? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Personalized medicine, a revolutionary approach in healthcare, aims to tailor medical treatments to individual patients based on their unique genetic, enviro...
Keywords: Precision Medicine and Genomics; Predict; Response; Based; Artificial Intelligence; Machine Learning; Deep Learning